Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

What is the constant term in the expansion of the binomial [tex]$(x-2)^4$[/tex]?

A. -16
B. 16
C. -32
D. 32


Sagot :

To determine the constant term in the expansion of the binomial [tex]\((x-2)^4\)[/tex], we can use the Binomial Theorem. The Binomial Theorem states:

[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]

In this case, [tex]\(a = x\)[/tex], [tex]\(b = -2\)[/tex], and [tex]\(n = 4\)[/tex]. The expansion of [tex]\((x-2)^4\)[/tex] can be written as:

[tex]\[ (x-2)^4 = \sum_{k=0}^{4} \binom{4}{k} x^{4-k} (-2)^k \][/tex]

We are specifically interested in the constant term in the expansion. The constant term is the term where there is no [tex]\(x\)[/tex] present, meaning [tex]\(x\)[/tex] must be raised to the power of 0. For this to happen, we need [tex]\(4-k = 0\)[/tex], that is, [tex]\(k = 4\)[/tex].

With [tex]\(k = 4\)[/tex], the constant term is:

[tex]\[ \binom{4}{4} x^{4-4} (-2)^4 \][/tex]

Simplifying each part, we have:

[tex]\[ \binom{4}{4} = 1 \][/tex]

[tex]\[ x^0 = 1 \][/tex]

[tex]\[ (-2)^4 = 16 \][/tex]

Therefore, the constant term is:

[tex]\[ 1 \cdot 1 \cdot 16 = 16 \][/tex]

So, the constant term in the expansion of [tex]\((x-2)^4\)[/tex] is:

[tex]\[ \boxed{16} \][/tex]

Hence, the correct answer is B. 16.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.